The Academic Dropout Wheel Analyzing the Antecedents of Higher Education Dropout in Education Studies - Hind Naaman (Foxton Books, 2021)
Higher education dropout has been considered a major concern for several researchers in the field of education around the World. Although different studies were carried out to deal with the topic, they all faced common limitations. This paper explores the twofold research conducted to investigate higher education dropout in Education studies at two of the main Catalan public universities. First, a review of the different theoretical perspectives that tackled dropout was carried out to combine the direct and indirect dropout predictors. Second, some research was conducted in the faculties of Education in the selected two Catalan public universities to investigate the antecedents of higher education dropout. The utilized instrument discussed in this paper is the survey. In the first part, the predictors of higher education dropout were combined in a 5-layer model called the ¨Dimensions of Academic Dropout" wheel (Naaman, 2018). In the second part, the results of the survey analyzed quantitively revealed that dissatisfaction from the program and academic failure are the most important antecedents of higher education dropout in education studies in Catalonia.